Transient electromagnetic-thermal nondestructive testing : pulsed eddy current and transient eddy current thermography /: pulsed eddy current and transient eddy current thermography. (2017) - He, Yunze; Gao, Bin; Sophian, Ali; Yang, Ruizhen
No abstract available